2018
DOI: 10.1002/adbi.201800219
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Nanoparticle Vaccines for Cancer Therapy

Abstract: It is currently understood that, in order for a tumor to successfully grow, it must evolve means of evading immune surveillance. In the past several decades, researchers have leveraged increases in our knowledge of tumor immunology to develop therapies capable of augmenting endogenous immunity and eliciting strong antitumor responses. In particular, the goal of anticancer vaccination is to train the immune system to properly utilize its own resources in the fight against cancer. Although attractive in principl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 184 publications
(192 reference statements)
0
72
0
Order By: Relevance
“…Cell membrane–coated nanoparticles, with their unique properties, have recently been leveraged in the design of anticancer vaccines . RBC‐NPs are known for their reduced host immune interactions and have been used extensively as a delivery vehicle .…”
Section: Biomimetic Anticancer Nanovaccinesmentioning
confidence: 99%
“…Cell membrane–coated nanoparticles, with their unique properties, have recently been leveraged in the design of anticancer vaccines . RBC‐NPs are known for their reduced host immune interactions and have been used extensively as a delivery vehicle .…”
Section: Biomimetic Anticancer Nanovaccinesmentioning
confidence: 99%
“…Unlike traditional vaccines, which boost the body's immune system to prevent infections, cancer vaccines boost the immune system to attack existing cancer cells [14]. Several anticancer vaccines have been processed in clinical trials, such as dendritic cell (DC) treatment for glioblastoma (NCT01808820), peptide vaccines for recurrent glioblastoma (NCT02754362) and whole-cell vaccines for breast cancer (NCT00317603), yet the limited ability to generate strong antitumor responses has hindered their wide application [15]. Therapeutic cancer vaccines should induce targeted killing of tumor cells as well as long-lasting immune protection against tumor recurrence or metastasis.…”
Section: Lymph Node-targeting Nanovaccinesmentioning
confidence: 99%
“…These NPs were stable and persisted in the structure during cellular endocytosis, activating the maturation of dendritic cells (DCs) and presenting especially to T cells that have TCR binding to gp100 and inducing the production of IFN-g. Moreover, the authors found that the PLGA covering membrane had receptors that allow interaction with cancer cells and delivery of the drug [4,5]. Furthermore, the NPs were used to deliver drugs to the specific site of organ transplantation to prevent rejection.…”
Section: Chapter Outline 11 Introductionmentioning
confidence: 99%